A Mathematical Model for Determining the Specific Structural Weight of a Tillage Implement - A. I. Derepaskın; А. N. Kuvaev; I. V. Tokarev (Сельскохозяйственные машины и технологии)
The authors have shown that the tillage specific constructive weight affects the working width and penetration ability. In order to increase the working width of the tillage implement, and therefore its performance and economic efficiency as well as its penetration ability, it is preferable to minimize the value of this indicator. It is taken into account that the implement specific structural weight will depend on the actual number of working tools and frame elements per unit of the working width. (Research purpose) The aim of the work is to develop a mathematical model to determine the minimum allowable and actual specific structural weight depending on the tillage implement operating conditions and its structural design and technological scheme. (Materials and methods) The research methodology is based on mathematical modeling, abstraction, analysis, synthesis, and principles of classical mechanics. (Results and discussion) The proposed mathematical model for determining the minimum allowable and actual specific structural weight was developed. The model takes into account the physical and mechanical characteristics of the cultivated soil, the number of working bodies and frame elements per unit of the tillage implement working width. It was found out that an increase in the working width makes it possible to reduce the implement actual specific structural weight, all other things being equal. It was proposed to use the mathematical model for designing tillage tools, carrying out force calculations and comparative assessment of metal consumption, depending on the installation and location of working bodies with different working widths. (Conclusions) It was found out that with the soil ultimate compressive strength of 100,000 pascal, the implement minimum allowable structural weight should be 334 kilograms per meter to ensure the tillage tool penetration to a given depth. Under the considered conditions, the implement actual specific structural weight will have a minimum value at the working width of 0.7 and 0.8 meters – 375 kilograms per meter and 335 kilograms per meter, respectively.